2017
DOI: 10.1016/j.dci.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of apolipoprotein genes and their involvement in disease response of channel catfish after bacterial infection

Abstract: Apolipoproteins are protein component of plasma lipoproteins. They exert crucial roles in lipoprotein metabolism and serve as enzyme cofactors, receptor ligands, and lipid transfer carriers in mammals. In teleosts, apolipoproteins are also involved in diverse processes including embryonic and ontogenic development, liver and digestive system organogenesis, and innate immunity. In this study, we identified a set of 19 apolipoprotein genes in channel catfish (Ictalurus punctatus). Phylogenetic analysis and synte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Lipid metabolic reprogramming is a known hallmark of cancer, and it has been shown that inhibition of cholesterol production with statins in head and neck cancers is associated with improved disease-specific survival [37]. In animal studies, ApoF has also been associated with immune and inflammation responses [38]. Transcription of interferon alpha (IFNα) responsive genes was shown to be impaired in the ApoF knockout mice and attributable also to hypomorphic expression of Stat2 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolic reprogramming is a known hallmark of cancer, and it has been shown that inhibition of cholesterol production with statins in head and neck cancers is associated with improved disease-specific survival [37]. In animal studies, ApoF has also been associated with immune and inflammation responses [38]. Transcription of interferon alpha (IFNα) responsive genes was shown to be impaired in the ApoF knockout mice and attributable also to hypomorphic expression of Stat2 [39].…”
Section: Discussionmentioning
confidence: 99%
“…Both the mRNA and protein levels of LAL2 were primarily expressed in liver, leukocytes, and kidney of the lamprey, which differed from the tissue distribution observed for apolipoprotein expression in teleost fish. For example, most apolipoprotein genes exhibited tissue-specific expression patterns in intestine, liver, and skin of channel catfish (35). Moreover, human apoa1, apoa4, and apoc3 have been cloned in fetal intestine and adult liver but not in fetal liver, kidney, heart, brain, or muscle (36).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoproteins are components of lipoproteins and the complexes they form depend on the species. They have lipid binding and transport functions in the lymphatic and circulatory systems and also have a role in immune responses to pathogen infection (Concha et al 2004;Yang et al 2017;Kondo et al 2005).…”
Section: Peptides With Other Structuresmentioning
confidence: 99%